Organizational Transformation / How to Achieve It and One Person at a Time - Avolio Bruce J. (Stanford University Press, 2018)
This book provides leaders and human resource professionals with invaluable insights they will find easy to digest and apply for impactful change. Acknowledgements, Preamble, Building the Narrative, First Principle: Changing the Self - Concepts, The Four - State Model, The Identifying State: The Signal for Change, The Initiating State: Beginning the Launch, The Impending State: Breaking Better, The Institutionalizing State: Defining 'My Organization', A Tale of Two Transformations, Becoming the Change and Sustaining It, Developing as a Transformative Leader, Notes, Index.